JOULE HEAT CALCULATION IN POROUS ALUMINA BARRIER LAYER DURING ELECTROCHEMICAL ANODIZING PROCESS - P. .. Katsuba; A. .. Leshok; V. .. Vysotskiy; S. .. Lazarouk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Heat-segregation calculations inside porous alumina barrier layer have been performed. It is shown that Joule heat on pore bottom surface is four orders of magnitude greater than in other porous oxide areas. This effect leads to local heating of this areas and microplasma formations during anodizing process. The recommendations about the heat dissipation efficiency increasing in order to improve the uniformity of the structures have been advised.